Serum Lactate Dehydrogenase Level in Pregnancy Induced Hypertension and Fetomaternal Outcome - Prajapati, Sarmila; Manandhar, Bekha Laxmi; Maskey, Suvana; Sharma, Jyoti (Nepal Medical College Journal, 2021)
Hypertensive disorders complicate 5-10% of all pregnancies and associated with potentially dangerous maternal and fetal complications. Studies have shown that pre-eclamptic patients with higher levels of lactate dehydrogenase (LDH) are at high risk of developing subsequent complications with poor maternal and fetal outcome. So with the aim to correlate serum LDH level in pregnancy induced hypertension (PIH) with fetomaternal outcome this hospital based observational descriptive study was done at Tribhuvan University Teaching Hospital (TUTH) for the duration of 1 year from 15th May, 2018 to 14th May, 2019. Women with PIH fulfilling inclusion criteria were enrolled in the study. Serum LDH level was measured and severity of PIH, maternal and perinatal outcome were studied according to the levels of LDH. Results were analyzed using SPSS 18. The incidence of hypertensive disorder in pregnancy was 4.74% in this study and total 180 cases were enrolled. The mean serum LDH level increased with increase in severity of PIH. Thirty two (17.7%) cases had maternal complications and hemolysis elevated liver enzymes and low platelet (HELLP) syndrome was most common complication. More than 2/3rd (62.5%) of cases with LDH level >800 IU/L had complications. The most common perinatal complication was intrauterine growth restriction (IUGR). The perinatal morbidity and mortality were significantly high in patients with PIH with LDH level >800 IU/l. As with the increase in serum LDH level increase in maternal and fetal complications was observed, LDH can be a useful biochemical marker that reflects the severity of PIH.